Categories of alcohol outcome expectancies and their relationships to alcohol related consequences. (June 2015) - Blume, Arthur W.; Guttu, Brady L.
Abstract: Extensive research has generally supported a significant and positive relationship of positive outcome expectancies with the amount of alcohol consumed among young adult drinkers, a group generally considered at high risk. Researchers have also naturally been interested in the relationships between these beliefs about drinking and the negative consequences experienced among those who abuse alcohol. Interestingly, those studies found significant positive associations of the number of alcohol outcome expectancies with drinking related consequences, independent of the amount of alcohol being consumed, suggesting that some consequences may be a function of beliefs rather than chemical effects. In addition, there has been evidence that age related differences may exist in the experience of positive outcome expectancies and their associations with consumption. One area that has not been examined is how different categories of alcohol outcome expectancies may be associated with different types of consequences among young adults. Young adults between ages 18–30 were assessed for different categories of alcohol outcome expectancies as well as different types of alcohol consequences. Study hypotheses were partially supported in that specific categories of expectancies were significantly associated with different types of consequences in multiple regression models, but not in the pattern that was predicted from a review of the literature. Expectancies with themes of personal power were consistently found to be significantly and positively associated with various types of consequences after controlling for alcohol consumption. The paper discusses the clinical relevance of these findings with regard to young adult drinkers. Highlights: Positive outcomes expectancies were significantly associated with various types of alcohol related consequences. The pattern of results may suggest the importance of considering positive expectancies associated with enhancing personal power. The clinical relevance of the study is discussed in the context of harm reduction and outcome expectancy challenges.